Exposure of the population of southern France to air pollutants in future climate case studies. (1st November 2021) - Cholakian, Arineh; Coll, Isabelle; Colette, Augustin; Beekmann, Matthias
Abstract: Population exposure to air pollutants varies dramatically with time and location on the globe. Taking into account the changing climate, the engaged emission reduction policies and the expected increase in population, the health risks associated with this phenomenon may also change significantly in the near future. In regions such as the Mediterranean, exposed to multiple forms of air pollution and highly sensitive to climate change, it is obviously critical to define trends in human exposure to air pollutants. The objective of this article is to explore the features of population exposure to air pollution in the French Mediterranean coast, under different climatic situations, using distinct emission configurations, and for divergent scenarios of population growth. The use of contrasting situations for these 3 parameters makes it possible to better address the variability of exposure in the different areas of the territory, as a global risk for populations. For this purpose, five 12 month-duration simulations have been carried out as case studies in the Provence Alpes Côtes d'Azur (PACA) region, located in the south-east of France: a 2005 simulation is used as the reference situation, and two more years of simulation are used as samples of time horizons 2030 and 2050, each of which was simulated twice sampling representative future climate years according to representative concentration pathway scenarios RCP4.5 and RCP8.5. Estimates of population change were prepared for the study area, using shared socioeconomic pathways (SSPs) scenarios. The results show that albeit the growing population, the exposure to most atmospheric components decreases because of emission reduction policies. This, however, is not true for all species. The population exposure to dust species increases for spring, when most dust episodes occur. In addition, exposure to ozone – while decreasing on the average - shows an increase in urban areas. Finally, while the concentrations of BSOA (secondary organic aerosol of biogenic origin) increase in the future scenarios, this tendency is not marked enough to offset the population decrease in rural areas in most SSP scenarios. On the reverse, exposure to BSOA does show an increase in urban areas where population is expected to grow. A county per county analysis is conducted, showing that the three coastal counties of the PACA region will experience higher ozone, PM10 and PM2.5, dust and BSOA exposure. The purpose of our work is to produce a case study in which we compare pollutant concentration changes and population weighed exposure changes on a meteorological situation that goes out of the current distribution. For this case study, we propose to distinguish the part of exposure changes due pollutant concentration and population changes. The choice of the study case (weather and horizon) is discussed in the text. This approach differs from the scenario approach, which focuses on the analysis of a trend representative of future years. Highlights: Clarification on the fact that we have chosen to perform case studies and not future scenarios Clarification on the choice made for the years simulated and the method used for this choice Organization of the sections: separating results from the methodology Adding references to corroborate several points raised by the reviewer Changes to the visibility of the axes in the images Some general proof-reading changes Clarification on the county-per-county analysis